Tinjauan Fatwa MUI Terhadap Penggunaan Hasil Produksi Alkohol di Sentra Industri Alkohol Bekonang - Moh Khairul Anam (Rechtenstudent, 2021)
The advanced of technology and the era of global trade, affecting the number of circulation local and imported products around us. The most dangerous and widely circulating hazardous material as a mixture of industrial products is alcohol. Alcohol or ethanol production is carried out at the Bekonang alcohol industry center by fermentation and distillation that used for medical purposes, but some of the entrepreneurs tend to produce 25% alcohol or commonly called ciu which is categorized as liquor. This research was aimed to find out the practice of alcohol production in Bekonang Village, Mojolaban District, Sukoharjo Regency and the Fatwa MUI review of alcohol production practices. This study uses field research methods using a qualitative approach. The results of this study indicate that the practice of alcohol production in Sentul Village, Bekonang Village, Mojolaban District, Sukoharjo Regency processed by fermentation until distillation produces 90% alcohol or ethanol used for health. In the review of the Fatwa MUI the product of the alcohol or ethanol production process in Bekonang Village is not from Khamr, so that its use is still allowed as long as it does not cause kemudaratan. So the center of the alcohol industry in Sentul Village Bekonang Village is not the khamr industry but the pure alcohol or ethanol industry, where the production is not for drinking but for health.